2004
DOI: 10.1098/rspb.2004.2678
|View full text |Cite
|
Sign up to set email alerts
|

Costs of immunity: immune responsiveness reduces survival in a vertebrate

Abstract: Immune defences are undoubtedly of great benefit to the host, reducing the impact of infectious organisms. However, mounting immune responses also entails costs, which may be measured by inducing immune responses against artificial infections. We injected common eider (Somateria mollissima) females with three different non-pathogenic antigens, sheep red blood cells (SRBC), diphtheria toxoid and tetanus toxoid, early in their incubation period. In the group of females that mounted a humoral immune response agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
212
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(221 citation statements)
references
References 41 publications
8
212
0
1
Order By: Relevance
“…In the immune-challenged group (nZ14), we measured the specific antibody responses against the antigens diphtheria and tetanus toxoids, respectively (for a detailed description of ELISA method in eiders, see Hanssen et al 2004). The females were injected with 150 ml diphtheria-tetanus vaccine in the pectoral muscle (SBL Vaccin AB, Stockholm; diphtheria toxoid 38 Lf (flocculation entities) and tetanus toxoid 7.5 Lf mixed with the adjuvant aluminium phosphate 5 mg ml K1 ).…”
Section: (B) Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the immune-challenged group (nZ14), we measured the specific antibody responses against the antigens diphtheria and tetanus toxoids, respectively (for a detailed description of ELISA method in eiders, see Hanssen et al 2004). The females were injected with 150 ml diphtheria-tetanus vaccine in the pectoral muscle (SBL Vaccin AB, Stockholm; diphtheria toxoid 38 Lf (flocculation entities) and tetanus toxoid 7.5 Lf mixed with the adjuvant aluminium phosphate 5 mg ml K1 ).…”
Section: (B) Immune Responsesmentioning
confidence: 99%
“…Female common eiders are cryptic brown with two white wing bars consisting of depigmented feather fringes (ranging in size from 0 to 6 mm; figure 1; Carney 1992). Female eiders incubate their eggs and care for the young alone or in cooperation with other females (Hanssen et al 2004;Hanssen 2006). Reproductive costs are large in common eiders.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that mounting an immune response is itself energetically costly because the metabolic requirements of immune cells and the indirect consequences of immune upregulation divert resources from other functions such as reproduction (Sheldon & Verhulst 1996;Ilmonen et al 2000;Bonneaud et al 2003) and survival (Hanssen et al 2004). Furthermore, it has been suggested that in natural populations parasites critically increase the rate of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Global climate change and increased habitat fragmentation are of increasing concern for conservation efforts (Austin et al, 2006;Drever et al, 2012) and may affect the dispersal of hosts and parasites, thereby altering their interactions and disease dynamics at different scales (Holt & Boulinier, 2005). Considering the temporal proximity of the spring migration and breeding seasons, energetic and behavioural costs of immune responses to varying helminth infections may lead to reduced survival and/or productivity (Hanssen et al, 2004;Stafford et al, 2014). Differences in parasite infracommunities between years was likely due to weather-related factors influencing the timing and duration of scaup migration, and the chronology, emergence and viability of intermediate hosts and the parasites they harbour.…”
Section: Spatiotemporal Assessmentmentioning
confidence: 99%